Determining CO2 storage potential during miscible CO2 enhanced oil recovery: Noble gas and stable isotope tracers. (August 2016) - Shelton, Jenna L.; McIntosh, Jennifer C.; Hunt, Andrew G.; Beebe, Thomas L.; Parker, Andrew D.; Warwick, Peter D.; Drake, Ronald M.; McCray, John E.
Highlights: Four active enhanced oil recovery (EOR) projects were sampled for fluids. The injected natural CO2 is likely a mix of crustal- and mantle-sourced gas. Isotopes did not prove to be useful tracers of CO2 storage in active EOR sites. All retained CO2 could be justified as stored in the target formations. Abstract: Rising atmospheric carbon dioxide (CO2 ) concentrations are fueling anthropogenic climate change. Geologic sequestration of anthropogenic CO2 in depleted oil reservoirs is one option for reducing CO2 emissions to the atmosphere while enhancing oil recovery. In order to evaluate the feasibility of using enhanced oil recovery (EOR) sites in the United States for permanent CO2 storage, an active multi-stage miscible CO2 flooding project in the Permian Basin (North Ward Estes Field, near Wickett, Texas) was investigated. In addition, two major natural CO2 reservoirs in the southeastern Paradox Basin (McElmo Dome and Doe Canyon) were also investigated as they provide CO2 for EOR operations in the Permian Basin. Produced gas and water were collected from three different CO2 flooding phases (with different start dates) within the North Ward Estes Field to evaluate possible CO2 storage mechanisms and amounts of total CO2 retention. McElmo Dome and Doe Canyon were sampled for produced gas to determine the noble gas and stable isotope signature of the original injected EOR gas and to confirm the source of this naturally-occurring CO2 . As expected, the natural CO2 produced from McElmo Dome and Doe Canyon is a mix of mantle and crustal sources. When comparing CO2 injection and production rates for the CO2 floods in the North Ward Estes Field, it appears that CO2 retention in the reservoir decreased over the course of the three injections, retaining 39%, 49% and 61% of the injected CO2 for the 2008, 2010, and 2013 projects, respectively, characteristic of maturing CO2 miscible flood projects. Noble gas isotopic composition of the injected and produced gas for the flood projects suggest no active fractionation, while δ 13 CCO2 values suggest no active CO2 dissolution into formation water, or mineralization. CO2 volumes capable of dissolving in residual formation fluids were also estimated along with the potential to store pure-phase supercritical CO2 . Using a combination of dissolution trapping and residual trapping, both volumes of CO2 currently retained in the 2008 and 2013 projects could be justified, suggesting no major leakage is occurring. These subsurface reservoirs, jointly considered, have the capacity to store up to 9 years of CO2 emissions from an average US powerplant.